African communication systems and the digital age - Akpabio, Eno (London, England ; New York, New York : Routledge, 2021)
The book covers African communication systems, discussing modes and forms of communication across West, East and Southern Africa and comparing them with traditional and new media. African Communication Systems and the Digital Age contextualizes communication by bringing to the table African contributions to the field, examining the importance of African indigenous forms of communication and the intersection of African communication systems and the digital age. The book covers various concepts, models, theories and classifications of African communication systems, including instrumental communication, types of African music and their communication properties, indigenous writing systems, non-verbal communication, and mythological communication. Through careful analysis of communication in Africa, this book provides insights into the various modes of communication in use prior to the advent of traditional and new media as well as their continued relevance in the digital age. African Communication Systems and the Digital Age will be of interest to students and scholars of African communication.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Communication -- Africa, Southern; Communication -- Africa, East; Communication -- Africa, West; LANGUAGE ARTS & DISCIPLINES / Communication